The teratogenic effect of dimefluthrin-based mosquito coils on pregnant mice (Mus musculus L.) - Efrizal,; Ikbal, Chika Afrilia; Jannatan, Robby (Penerbit Universiti Kebangsaan Malaysia, 2024)
Dimefluthrin, a synthetic pyrethroid insecticide, claims to be safe and harmless to mammals. However, the potential risk of mosquito coils containing dimefluthrin to pregnant mice remains uncertain. This study aimed to examine the teratogenic effect of dimefluthrin when inhaled by pregnant mice at different stages of gestation. The study used mosquito coils with 0.031% dimefluthrin as the active ingredient and was exposed to pregnant mice at various pregnancy stages. The results revealed that mosquito coils with dimefluthrin had teratogenic effects, reducing the number of live fetuses and increasing the number of dead fetuses, especially from the seventh to the eighteenth day of pregnancy. Additionally, there was a decrease in fetal weight, length, and volume, particularly during the seventh to eighth day of gestation. Hemorrhages were observed as fetal abnormalities and were highest three hr after exposure every day during pregnancy. The conclusion of this research is pregnant mice exposed to mosquito coil smoke containing dimefluthrin experienced a decrease in the number of live fetuses and an increase in fetal mortality. While there was no significant impact on reabsorption, the fetuses showed reduced weight, and size, and an increased incidence of hemorrhages when exposed for three hr daily during pregnancy.